Queer 1950s
XIII, 209 p.
Keywords: Leading sexuality scholars explore queer lives and cultures in the first full post-war decade through an array of sources and a range of perspectives. Drawing out the particularities of queer cultures from the Finland and New Zealand to the UK and the USA, this collection rethinks preconceptions of the 1950s and pinpoints some of its legacies.